Synthesis and Antibacterial Studies of Phenethylamine Alkaloid Natural Products Along with Their Analogues: Discolin A, B, E and Bacillimidazole B - Khatua, Rashmi Ranjan; Ahmad, Sarwat Asma Ziya; Das, Susmita; Anindya, Roy; Khan, Faiz Ahmed (Synlett, 2024)
The first total synthesis of phenethylamine alkaloid based natural products discolin A, B, E and bacillimidazole B is reported, which were isolated from marine sea bacteria Tenacibaculum discolor sv11 and marine sponge. Total syntheses of discolin A, B, E and bacillimidazole B are achieved in two linear steps including condensation reaction and N-alkylation reaction with an overall yield of 68%, 35%, 65%, and 32%, respectively. A total of 24 analogues are prepared with moderate to excellent yield. All the natural products and their analogues were screened for antibacterial activity. The most active compound showed an IC50 of 122.1 nM against P. aeruginosa.
Keywords: discolin; marine bacteria; natural product; imidazole; antimicrobial; bacillimidazole